ποικιλόνωτος ἀνήρ: Clothing Metaphors and Nonnus’ Ambiguous Christology in the "Paraphrase of the Gospel according to John" - Hadjittofi, Fotini (Vigiliae Christianae, 2018)
This article examines three passages in Nonnus’ Paraphrase of the Gospel according to John (19.21-25; 19.118-132; 20.81-82), all of which mention pieces of clothing in the context of Christ’s passion and resurrection. It argues that Nonnus allows, and indeed encourages, both literal readings and metaphorical interpretations of the garments as stand-ins for Christ’s body. The readings which do not turn garments into symbols of the body would be more in agreement with the Orthodox theology of Nonnus’ time, while the metaphorical interpretations would be more amenable to a heterodox (Origenist or Nestorian) construal. The poem’s ambivalence in the employment of clothing metaphors indicates an attitude that is less strictly Alexandrian / Orthodox and more polyphonic than has so far been assumed.